METHODOLOGY FOR CONTROLLING TRAINING LOADS OF HIGHLY SKILLED BELT WRESTLERS - Isakov Shuxratbek Muydinovich (Research Focus International Scientific Journal, 2023)
in this article, the development of a two-month planning methodology for training loadings, taking into account the content and dynamics of nagruzkas, the direction of which is specialized in the Greco-Roman struggle, has been created to optimize the training process, as well as provide information on the effectiveness of the preparation of Greco-Roman wrestlers for Responsible competitions.